Motivational factors of women to become social entrepreneurs in Lundu district, Sarawak - Yee, Lai Ling; Johari, Shazali; Emang, Diana; Thoo, Poh Yee; Hasan, Muhammad Luqman (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Social entrepreneurship has become the attention of the scholars and practitioners for years in various countries as it is a tool which plays important roles in developing individuals, societies, and communities socially and economically. However, it is essential to study the motivations of the social entrepreneurs as it is yet to be theorised. Therefore, this study is to determine what motivates the women to become social entrepreneurs. A set of designed questionnaires with dual languages was used for the data collection. Motivational factors were measured on respondents’ agreement by using five-point Likert Scale. This study was targeted at women social entrepreneurs in Lundu District, Sarawak. The data collected was analysed by using the IBM SPSS. Through the samples of 150 women social entrepreneurs, the findings show that “Financial Independence” is the motivational factor that motivates women the most, which followed by “Contribution to Society” and “Need for Affiliation”. On the other hand, “Role Models Influence” is the least motivational factor for the women to join the ventures in social entrepreneurship. In a nutshell, this study provides the picture on what motivates the social entrepreneurs which can then be the reference for management to design strategies to attract more people to join social entrepreneurship as well as the reference for future related studies.